From Numbers to Victory Laps: Accelerating Grade 8 Students’ Numeracy Skills Using a Modified Math Racetrack Board Game - Tambong, Christian (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study was conducted to investigate the effectiveness of the Modified Math Racetrack Board Game in accelerating the numeracy skill level of 35 Grade 8 students at Lilo-an National High School for School Year 2024-2025, utilizing a mixed-methods quasi-experimental research design with a one-group pretest-posttest approach. Quantitative data were collected through the Enhanced Regional Unified Numeracy Test (E-RUNT), prescribed by the Department of Education, which was administered before and after a 5-week intervention program, while qualitative data were gathered through a Focus Group Discussion (FGD) among 8 purposively selected students. Research findings revealed that during pretest, majority of the students were categorized as Low Proficient and Non-Proficient with an over-all mean score of only 17.49 (Low Proficient). After the intervention program, posttest results significantly improved, with a substantial number of students already classified as Proficient and Highly Proficient with an over-all mean score of 30.60 (Proficient), yielding a mean difference of 13.11. The paired samples t-test indicated a statistically significant difference between the pretest and posttest scores (p = .000), signifying the effectiveness of the Modified Math Racetrack Board Game did not occur by chance. Qualitative findings strengthen these results, as students described the board game enjoyable, exciting, and fun, motivating, promoted independent learning and more preferred over traditional activities. Therefore, this study directly contributes to United Nations Sustainable Development Goal 4 (Quality Education) by promoting inclusive and equitable quality education through an innovative, learner-centered instructional intervention that enhances foundational numeracy skills essential for lifelong learning.